2008
DOI: 10.1111/j.1399-0004.2008.00999.x
|View full text |Cite
|
Sign up to set email alerts
|

Silent exonic mutations in the low‐density lipoprotein receptor gene that cause familial hypercholesterolemia by affecting mRNA splicing

Abstract: In a large group of patients with the clinical phenotype of familial hypercholesterolemia, such as elevated low-density lipoprotein (LDL) cholesterol and premature atherosclerosis, but without functional mutations in the genes coding for the LDL receptor and apolipoprotein B, we examined the effect of 128 seemingly neutral exonic and intronic DNA variants, discovered by routine sequencing of these genes. Two variants, G186G and R385R, were found to be associated with altered splicing. The nucleotide change lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…Many different human diseases can be caused by errors in mRNA splicing or its regulation. Interestingly, intronic deletions causing exon skipping or intron retention in the human LDLR gene were identified in patients with familial hypercholesterolemia (4,9,12,22,40). Because the human LDLR gene is homologous to the chicken tva gene, it is tempting to speculate that this is a common mechanism of mutagenesis within this gene family.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many different human diseases can be caused by errors in mRNA splicing or its regulation. Interestingly, intronic deletions causing exon skipping or intron retention in the human LDLR gene were identified in patients with familial hypercholesterolemia (4,9,12,22,40). Because the human LDLR gene is homologous to the chicken tva gene, it is tempting to speculate that this is a common mechanism of mutagenesis within this gene family.…”
Section: Discussionmentioning
confidence: 99%
“…The same intronic deletions were also found in a subspecies of red jungle fowl, Gallus gallus murghi. The frequent disrup-tion of splicing signals resembles the situation in the low-density lipoprotein receptor gene, a human homologue of chicken tva, in patients with familial hypercholesterolemia (12,40). We conclude that ASLV receptor alleles determining the decreased sensitivity to avian retroviruses are common in the population of domestic chick as well as in wildfowl and could play an important role in virus-host coevolution.…”
mentioning
confidence: 87%
“…Analysis of mRNA from the patient's cells showed that the mutation introduces a new splice site, which is used to the exclusion of the natural splice site and causes a deletion of 31 bp from the mRNA, predicted to introduce premature termination four codons after Arg406 (p.Ser397Thrfs à 6). In 2008, a Dutch group published another synonymous variant, c.621C>G, p.(Gly207Gly), as cause of splicing defect [50]. A novel synonymous variant c.1813C>T, p.(Leu605-Leu) has been recently characterized as having an effect on splicing [51 & ], introducing also a premature stop codon.…”
Section: Putative Splicing Variantsmentioning
confidence: 99%
“…Five variants, c.1246AϾC, c.1448CϾT, c.1740GϾA, c.2130CϾT, and c.2229AϾG, are silent mutations. However, a potential effect on gene splicing [37][38][39] or on protein function 40 cannot be ruled out. Seven homozygous variants were also included in the HRM variant panel.…”
Section: Hrm Analysis Of Patient Samples With Variants Detected In Thmentioning
confidence: 99%